2022
DOI: 10.17977/um002v14i22022p214
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency Analysis of MSMEs Fashion Offline and Online in Surabaya

Abstract: The main purpose of this study is analyzing the level of technical efficiency of MSMEs fashion offline with offline and online in Surabaya, examine the differences between offline with offline and online, and determine the factors that affect technical efficiency. This study uses purposive sampling method with primary data. Non-parametric and parametric approach used with Data Envelopment Analysis, Independent sample T-Test and Tobit Regression. First, the results showed the average level of technical efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Research has shown that business owners in Indonesia and other places quickly turned to apps and live streaming on sites to cope with the pandemic's challenges (Raco et al, 2021). This move was especially beneficial for the fashion industry, where live streaming changed how products are promoted and how shops talk to customers (Purmiyati et al, 2022).…”
Section: Smes In Indonesiamentioning
confidence: 99%
“…Research has shown that business owners in Indonesia and other places quickly turned to apps and live streaming on sites to cope with the pandemic's challenges (Raco et al, 2021). This move was especially beneficial for the fashion industry, where live streaming changed how products are promoted and how shops talk to customers (Purmiyati et al, 2022).…”
Section: Smes In Indonesiamentioning
confidence: 99%